A Town like Alice - Shute, Nevil (Heinemann Publishers (Oxford) Ltd, 1950)
1940, Malaya. The war is on. A group of women and children are captured by the Japanese. This is the story of their long march through Malaya and a search for love that ends in Australia.
Keywords: Juvenile Fiction